The Implementation Of Education Management Standards In Improving The Quality Of Graduates Of Madrasah Tsanawiyah In Karawang - Ansori, Ansori; Ulfiah, Ulfiah; Sudrajat, Adjat; Syaodih, Cahya (CV. Inara, 2022)
This research background is the implementation of education management standards that have not been able to answer the needs and demands of the community regarding the quality of madrasah graduates. The purpose of this study is to investigate and obtain an overview about the implementation of education management standards in improving the quality of madrasah graduates through planning, implementation, evaluation, constraints and solutions. This study was conducted at two Madrasah Tsanawiyah Negeri of Karawang, West Java Province, namely MTs Al-Ahliyah Karawang and MTs Negeri 5 Karawang. The method used is qualitative approach with descriptive analytics methods, and data collection uses observation, interviews, and documentation studies. Research findings reveal that the implementation of Education Management Standards at MTs Al-Ahliyah Karawang Regency and MTs Negeri 5 Karawang has been going well but cannot be said to be optimal because there are several obstacles faced both internally including human resources, facilities and infrastructure, as well as external constraints in aspects of support from related parties. The implementation process goes through planning, implementing, evaluating, constraining and following up to produce graduates who have noble, superior and competitive morals so that many are accepted in high schools.